2018
DOI: 10.1002/gps.4918
|View full text |Cite
|
Sign up to set email alerts
|

General practitioners' knowledge, attitudes, and experiences of managing behavioural and psychological symptoms of dementia: A mixed‐methods systematic review

Abstract: ObjectivesTo synthesise the existing published literature on general practitioners (GP)'s knowledge, attitudes, and experiences of managing behavioural and psychological symptoms of dementia (BPSD) with a view to informing future interventions.MethodsWe conducted a systematic review and synthesis of quantitative and qualitative studies that explored GPs' experiences of managing BPSD (PROSPERO protocol registration CRD42017054916). Seven electronic databases were searched from inception to October 2017. Each st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 83 publications
(300 reference statements)
1
39
0
3
Order By: Relevance
“…Although older adults and terminally ill patients usually report preferring to die in their own homes, in regard to dementia, older adults also prioritize safety and supervision because of the impaired decision‐making capacity and behavioral changes associated with the condition . As many general practitioners are struggling to obtain the resources to address the behaviors and symptoms of dementia, middle‐aged adults might suppose that professional home care services are inadequate for people with dementia who require regular supervision . Some dementia‐care programs have been developed to help home‐care professionals address behavioral changes in dementia .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although older adults and terminally ill patients usually report preferring to die in their own homes, in regard to dementia, older adults also prioritize safety and supervision because of the impaired decision‐making capacity and behavioral changes associated with the condition . As many general practitioners are struggling to obtain the resources to address the behaviors and symptoms of dementia, middle‐aged adults might suppose that professional home care services are inadequate for people with dementia who require regular supervision . Some dementia‐care programs have been developed to help home‐care professionals address behavioral changes in dementia .…”
Section: Discussionmentioning
confidence: 99%
“…10 As many general practitioners are struggling to obtain the resources to address the behaviors and symptoms of dementia, middle-aged adults might suppose that professional home care services are inadequate for people with dementia who require regular supervision. 26 Some dementia-care programs have been developed to help home-care professionals address behavioral changes in dementia. 27 National dementia policies should make such programs available for people living with dementia in their own homes, as well as those in nursing homes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] In a study conducted by Cousins, Bereznicki, Cooling and Peterson (2017), [14] it was found that nurses and family members strongly influence medical practitioners towards prescribing psychotropic medications, as nearly half of the sample felt that they required increased training of BPSD to manage symptoms using nonpharmacological methods, and thus reducing the use of psychotropic drugs. Similarly, Jennings et al (2018) [15] found that general practitioners felt a lack of knowledge of BPSD and their management using multiple treatment modalities, which likely contributes to the heavy reliance on pharmacotherapy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Flexibility can be applied by providing frameworks or directions rather than step-bystep instructions or a combination of both while maintaining a contained setting or time and place for the intervention such as a session. 13 While reviews have been conducted to assess the availability and effectiveness of evidence-based training manuals and to inform the development of interventions, [14][15][16] the purpose of this scoping review is to learn from research studies which have taken on the challenge to construct manuals for complex interventions carried out by caregivers and tailored to the preferences, skills, and abilities of the person with dementia. With this review, we aim to stress the importance of availability of manuals through refereed journals in order to inform future research in dementia care and improve clinical interventions and care.…”
Section: Introductionmentioning
confidence: 99%